Analysis of Complete Genome Sequence of Acinetobacter baumannii Strain ATCC 19606 Reveals Novel Mobile Genetic Elements and Novel Prophage - Mohammad Hamidian; Lucia Blasco; Lauren N. Tillman; Joyce To; María Tomas; Garry S. A. Myers (Microorganisms, 2020)
Acinetobacter baumannii isolate ATCC 19606 was recovered in the US prior to 1948. It has been used as a reference and model organism in many studies involving antibiotic resistance and pathogenesis of A. baumannii, while, until recently, a complete genome of this strain was not available. Here, we present an analysis of the complete 3.91-Mbp genome sequence, generated via a combination of short-read sequencing (Illumina) and long-read sequencing (MinION), and show it contains two small cryptic plasmids and a novel complete prophage of size 41.2 kb. We also characterised several regions of the ATCC 19606 genome, leading to the identification of a novel cadmium/mercury transposon, which was named Tn6551. ATCC 19606 is an antibiotic-sensitive strain, but a comparative analysis of all publicly available ST52 strains predicts a resistance to modern antibiotics by the accumulation of antibiotic-resistance genes via plasmids in recent isolates that belong to this sequence type.